2015
DOI: 10.1515/bsmr-2015-0025
|View full text |Cite
|
Sign up to set email alerts
|

The Undercurrents of Estonian Broadcasting Regulation, 1992–2014

Abstract: This article explores the ways in which diff erent external and internal factors (especially politics and economics) have encouraged or hindered the evolution of Estonian Public Broadcasting. This article argues that the Estonian government's 'idealisation' of market forces that is supported by European Union (EU) media policy and driven by the common market ideology does not take into account the actual abilities of a small country's media companies to provide a wide range of media services, and thereby limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…These factions can be characterised, and their conflicts shaped, by different ideological frameworks, specialised knowledge systems or reference groups (with different degrees of empowerment) and associated path dependencies or contingencies. In the specific case of the evolution of media policy in Estonia, this article identifies the ideological path dependencies in the participating governmental institutions and recognises that this is comprised partly of the ideological lock-ins that cause Estonia's cultural policy goals to be sacrificed for other goals, such as broad market liberalisation and normative globalisation in the digital services sector, which is now perceived to include audiovisual culture (see Jõesaar, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These factions can be characterised, and their conflicts shaped, by different ideological frameworks, specialised knowledge systems or reference groups (with different degrees of empowerment) and associated path dependencies or contingencies. In the specific case of the evolution of media policy in Estonia, this article identifies the ideological path dependencies in the participating governmental institutions and recognises that this is comprised partly of the ideological lock-ins that cause Estonia's cultural policy goals to be sacrificed for other goals, such as broad market liberalisation and normative globalisation in the digital services sector, which is now perceived to include audiovisual culture (see Jõesaar, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…What has also been established is the understanding that European media policy is increasingly driven by economic imperatives and less by cultural goals such as diversity or enlightenment (e.g. Celsing, 2010;Jõesaar, 2015). Further, the specific limitations on media markets in Europe's small member states have been evidenced in a series of works (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the changes are evident in the changes in the companies' profitability between 2002 and 2007. 42,43 Between 2004 and 2008, only a few new TV licences were issued, and all of them were local licences. OÜ Lites LT started the LiTeS programme in East-Virumaa in 2004; the non-profit AB Video started the TV-N programme on the Harjumaa and Tallinn cable network in late 2006 (it is now available throughout Estonia).…”
Section: T H E G O L D E N Ye a R Smentioning
confidence: 99%
“…The latter aspect tends to be a source of tensions since at the European level audiovisual policy issues are largely discussed from the perspective of broader market regulation (but Estonia's general view is for more liberalisation), and the cultural policy goals are deemed to be secondary. Therefore, it could be suggested that media convergence in the form of regulatory processes, especially the way European regulatory processes are structured in Estonia, tend to result in support for more market liberalisation (Jõesaar 2015); and all the traditional forms of audiovisual arts and culture are losing their specifi c status as cultural public goods that need special regulatory protection (especially with regard to securing the cultural diversity -i.e., the main aim of the system is to produce cultural innovations, resulting in a diverse cultural space). In other words, the Ministry of Economic Affairs and Communications has generally protected the interests of the broader market, especially internet freedom (i.e., free provision of services) and the interests of consumers at the expense of strengthening the national audiovisual industries.…”
Section: Institutions Andmentioning
confidence: 99%
“…The analysis in this article revealed three main tendencies. First, at the broadest level, especially when it comes to Estonia's position with regard to EU level policymaking, the country tends to prefer the strengthening of the market, especially the liberalisation of the internet economy, at the expense of securing the production of cultural diversity locally (also see Jõesaar 2015). This also means ignoring the need to strengthen the national audiovisual industry.…”
mentioning
confidence: 99%